External loads of elite soccer referees: A systematic review with meta-analysis - Preissler, A. V. B.; Reichert, T.; Schons, P.; Rocha Costa, R.; Sudatti Delevatti, R.; Denadai, B. S.; Kruel, L. F. M. (Research in Sports Medicine, 2023)
The objective of the present study was to describe the total and fragmented external loads, at different intensities, of soccer referees in European and South American competitions during official matches through a systematic review and meta-analysis of cross-sectional studies. A systematic review was conducted in April, 2020. In all, 32 studies were included, incorporating 578 referees evaluated in 3170 games through video analysis or a global positioning system. Regarding external loads, it was observed that the total average distance covered by the referees was 10,461.74 m, with running speeds predominantly below 13 km.h-1. The total distance covered by the referees in the European competitions was higher and more intense than that of the referees in the South American tournaments, being 11,187.02 m and 9319.61 m, respectively. We suggest that referees` training can be organized according to the distances found at different intensities, in which low-intensity races can be performed below 13 km.h-1 with distances of approximately 4500 m, while high-intensity training can be developed with speeds from 18 to 24 km.h-1 for approximately 800 m. In addition, planning must consider the competition characteristics.